Linear Elamite Deciphered! (Biblical archaeology review, 2022)
The article reports on the identification and deciphering of 72 different signs in Linear Elamite inscriptions by a team of scholars after recognizing similarities between Linear Elamite script texts and royal Elamite inscriptions.